Potential of the livestock industry environment as a reservoir for spreading antimicrobial resistance - Aswin Rafif Khairullah; Ikechukwu Benjamin Moses; Sheila Marty Yanestria; Fidi Nur Aini Eka Puji Dameanti; Mustofa Helmi Effendi; John Yew Huat Tang; Wiwiek Tyasningsih; Budiastuti Budiastuti; Muhammad Khaliim Jati Kusala; Dea Anita Ariani Kurniasih; Bantari Wisynu Kusuma Wardhani; Syahputra Wibowo; et al. (Open Veterinary Journal)
Antimicrobial resistance (AMR) in bacteria is a global issue that requires serious attention and management. Indiscriminate usage of antibiotics in livestock for growth promotion, disease prevention and treatment has led to the dissemination of AMR bacteria and resistance genes into the environment. Besides, unethical antibiotic sales without prescriptions, poor sanitation and improper disposal cause significant amounts of antibiotics used in livestock to enter the environment causing the emergence of resistant bacteria. Intensive livestock farming is an important source of AMR genes and environmental bacteria contamination and possible transfer to human pathogens. Bacteria intrinsic antibiotic resistant which are independent of antibiotic use further complicate the AMR issue and increase the risk of morbidity and mortality following infections from AMR bacteria. Escherichia coli, Salmonella spp., and Staphylococcus spp. are commonly found in livestock that carry resistance genes and the possibility of causing human infections. The impact of AMR, if left unchecked, could lead to substantial public health burdens globally with a predicted mortality rate higher than cancer by 2050. "One Health" integrates strategies across human, animal and environmental health domains, including improving antibiotic stewardship in livestock, preventing infection and raising awareness on the judicious use of antibiotics. Usage of antibiotic alternatives to control or prevent infections in livestock such as prebiotics, probiotics, bacteriophages, bacteriocins and vaccinations will help over-reliance on antibiotics. Coordinated international actions are needed to mitigate the spread of AMR through improved regulations, technology improvement, and awareness campaigns. [Open Vet J 2025; 15(2.000): 504-518]